The Role of Corneal Aberrations in the Development and Progression of Pseudophakic Myopia after Congenital Cataract Extraction in Infancy - L. A. Katargina; A. S. Galkina; T. B. Kruglova; S. V. Milash (Oftalʹmologiâ, 2023)
Relevance. Many studies have shown a relationship between higher order aberrations and refractive errors in children without comorbidities, but these studies have not been conducted in children with pseudophakia. Purpose. Evaluation of corneal aberrations after congenital cataract (CC) extraction with intraocular lens (IOL) implantation in infancy, and their impact on the dynamics of eye growth and myopia progression. Materials. Thirty-two children (the median age 9.35 ± 3.31 years; range 4–15 years) with pseudophakia were divided to: group 1, planned refraction (17 children, 23 eyes) and group 2, pseudophakic myopia (15 children, 23 eyes). Twelve children (24 eyes; the median age 11.67 ± 2.43 years) with moderate and high myopia without ophthalmic pathology were examined as a comparison group. Keratometry and aberrometry were performed on a Scheimpflug Galilei G2. Results. Total corneal aberrations root mean square (RMS) and higher order aberrations (HOA) were higher in pseudophakic children (2.77 and 1.13 µm in group 1, 2.48 and 1.15 µm in group 2) when compared with children with acquired myopia (1.58 and 0.44 µm; p < 0.05). Oblique astigmatism and negative oblique trefoil were the highest in pseudophakic myopia (0.63 and (-)0.48 µm). There were positive correlations between eye growth in 4 years and HOA (r = 0,699; p < 0,01), eye growth during the total follow-up time and oblique astigmatism (r = 0,393; p < 0,01), and negative correlation between eye growth during the total follow-up time and oblique trefoil (r = -0,322; p < 0,05). Conclusion. Corneal incision with forced corneal suture during surgery in infants leads to an increase in HOA, especially oblique astigmatism, and oblique trefoil. Correlations between corneal aberrations and the dynamics of globe axial length growth indicate the effect of monochromatic aberrations on eye growth already in the early postoperative period.